2022
DOI: 10.1080/10875301.2022.2029790
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Queries: Where Chat Reference Questions Begin

Abstract: Academic libraries providing chat reference services have a range of options for where and how library users can engage with chat providers. These entry points can be static or proactively invite users into the service. The study compares the URLs from which users entered chat reference at three large public research libraries the United States. The URLs show where users were when they sought assistance with library tasks. This exploratory investigation is important for extending knowledge of user help-seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several more studies found that WhatsApp and instant messaging usage frequency among university students increased because of their convenience, speed and textual record (Charbonneau and Vardell, 2022; Tsang and Chiu, 2022; Guo et al. , 2022; Hurley and Warner, 2022; Dempsey et al. , 2022; Sinhababu and Kumar, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several more studies found that WhatsApp and instant messaging usage frequency among university students increased because of their convenience, speed and textual record (Charbonneau and Vardell, 2022; Tsang and Chiu, 2022; Guo et al. , 2022; Hurley and Warner, 2022; Dempsey et al. , 2022; Sinhababu and Kumar, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Kumar and Gupta (2022) study the restructuring of library resources and services at IIT Delhi library and find that user usage and preferences for electronic resources and services are increasing. Several more studies found that WhatsApp and instant messaging usage frequency among university students increased because of their convenience, speed and textual record (Charbonneau and Vardell, 2022;Tsang and Chiu, 2022;Guo et al, 2022;Hurley and Warner, 2022;Dempsey et al, 2022;Sinhababu and Kumar, 2022). It was discovered by Borthakur and Sinha (2022) and Gupta (2022) that most respondents frequently searched for e-books, e-journals, e-theses, online databases, theses, dissertations and e-patents on the Internet.…”
Section: Literature Reviewmentioning
confidence: 99%